Shoulder and Hip Range of Motion and Strength Changes Throughout a Season in College Softball Players - Cameron R Guy; Giorgio Zeppieri Jr.; Michelle L Bruner; Katie Davis; Kevin W Farmer (International Journal of Sports Physical Therapy)
# Background